The Teacher’s Competency Development Model of Fine Arts in Universities Under Liaoning Province - Zhao Yue; Chanphong , Somsak; Howattanakul , Sutida (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were: (1) To study the components and variables of teacher’s competency model development of fine arts in universities under Liaoning province. (2) To propose the guideline for improving teacher’s competency development of fine arts in universities under Liaoning province. The research was a mixed methodology research. Population was fine arts teachers in universities under Liaoning Province, totaling 640 people, sample size 242. The sample size was determined by Krejcie and Morgan’s Table (1970 : 607-610) was obtained by stratified random sampling method, sample size was 242. The instruments used for data collection were semi-structured interview form, five-point rating scale questionnaires and focus group discussion form. The response rate of questionnaires was 100%. Statistics used for data analysis included frequency, percentage, mean, standard deviation, exploratory factor analysis, and content analysis. The research findings were revealed that (1) teacher’s competency development model of fine arts in universities under Liaoning province consisted of 7 components as follow, ego trait contains 15 variables, motivation contains 18 variables, self-concept contained 12 variables, emotional Competencies contains 18 variables, basic competency contains 15 variables, teaching competence contains 21 variables, and professional competence contains 15 variables; and (2) the guideline for improving teacher’s competency development model of fine arts in universities under Liaoning province. There were 27 guiding principles for improving teacher’s competency development model of fine arts in universities under Liaoning province.